2021
DOI: 10.1371/journal.pgen.1009593
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput framework for genetic analyses of adverse drug reactions using electronic health records

Abstract: Understanding the contribution of genetic variation to drug response can improve the delivery of precision medicine. However, genome-wide association studies (GWAS) for drug response are uncommon and are often hindered by small sample sizes. We present a high-throughput framework to efficiently identify eligible patients for genetic studies of adverse drug reactions (ADRs) using “drug allergy” labels from electronic health records (EHRs). As a proof-of-concept, we conducted GWAS for ADRs to 14 common drug/drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Thus, we suggest starting with semi-structured clinical notes (e.g. problem/medication lists): for example, recent studies have demonstrated the benefits of using allergy lists for clinical studies 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest starting with semi-structured clinical notes (e.g. problem/medication lists): for example, recent studies have demonstrated the benefits of using allergy lists for clinical studies 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…These are the 2 most common gene loci influencing majority drugs used in perioperative settings. 24 Such integrative studies, deriving phenotypes from the EHR and matching up with genomic testing, are increasing and gaining traction as an efficient means to identify selected patients, reduce costs, speed up diagnosis, and improve care. 25 Futurists and advocates of PM opine that the best way to assimilate the vastness of the field into clinical utility is by open-science and open-resource tools.…”
Section: Implementation Science and Societal Acceptancementioning
confidence: 99%